ANALYSIS OF VOCABULARY PROBLEMS FACED BY STUDENTS OF BS ENGLISH - Rahna Fatima; Faryal Bibi (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of the study “Analysis of vocabulary problems faced by students of BS English “is to identify the types and types of students' vocabulary difficulties in learning. The subjects of this study are speech students in the 7th semester of the English department at Kotli AJK University. This study used a research design that well demonstrates the characteristics of the study. Researchers use interviews and questions to obtain information. All data were analyzed descriptively. Research shows that students still face difficulties or problems learning the vocabulary. There are many challenges students face when learning a vocabulary. The difficulties students face are: Almost all students have speech problems.The way in which words are written and written, and the forms through which words of different grammatical types are linguistically transformed (called transformations). Students have difficulty learning languages. Additionally, students look at problems from Snow, John. Burns, Michael; And Griffin, Alex. 1998. Comment:: Longman The meaning of the word is appropriate and there is still confusion when using the word in context. Lastly, students also become confused when they see negative words or expressions. Factors that make it difficult for students to learn a vocabulary include the fact that written and spoken English are different, the number of words students must learn, and limited knowledge of English. Language, Difficulty recognizing words. Knowing a word is more than just knowing the definition, lack of understanding of the grammar of the word, there are phonetic similarities between English and the learner's native language, which are often caused by pronunciation.